2018
DOI: 10.1098/rspb.2018.1747
|View full text |Cite
|
Sign up to set email alerts
|

Estimating apparent survival of songbirds crossing the Gulf of Mexico during autumn migration

Abstract: Many migratory bird species are declining, and the migratory period may limit populations because of the risk in traversing large geographical features during passage. Using automated radio-telemetry, we tracked 139 Swainson's thrushes ( Catharus ustulatus ) departing coastal Alabama, USA and crossing the Gulf of Mexico to arrive in the Yucatan Peninsula, Mexico during autumn. We estimated apparent survival and examined how extrinsic (weather variables and day of year) and intrinsic (fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 57 publications
(77 reference statements)
3
49
0
Order By: Relevance
“…Given these results and those from recent studies with red knots (Leyrer et al, 2013;Rakhimberdiev et al, 2015), how strongly should migration be expected to determine the population dynamics of migratory species? Previous studies of migratory birds making flights across large geographic barriers, such as the Sahara, have found that mortality events experienced during these flights may result from a suite of potentially interacting and sometimes unpredictable processes, including extremely high temperatures (Schmaljohann et al, 2007), violent sandstorms (Klaassen et al, 2010), poor body condition (Ward et al, 2018), and predation (Gangoso et al, 2013). In some cases, the mortality events experienced during these flights play an important role in determining a species' overall population dynamics (Lok et al, 2013).…”
Section: Annual Cycle Eventmentioning
confidence: 99%
See 1 more Smart Citation
“…Given these results and those from recent studies with red knots (Leyrer et al, 2013;Rakhimberdiev et al, 2015), how strongly should migration be expected to determine the population dynamics of migratory species? Previous studies of migratory birds making flights across large geographic barriers, such as the Sahara, have found that mortality events experienced during these flights may result from a suite of potentially interacting and sometimes unpredictable processes, including extremely high temperatures (Schmaljohann et al, 2007), violent sandstorms (Klaassen et al, 2010), poor body condition (Ward et al, 2018), and predation (Gangoso et al, 2013). In some cases, the mortality events experienced during these flights play an important role in determining a species' overall population dynamics (Lok et al, 2013).…”
Section: Annual Cycle Eventmentioning
confidence: 99%
“…Given that trans-Saharan flights occupy such a short period of time, survival rates during these flights would have to be severely reduced before they become the limiting component of the godwit annual cycle (but see Sillett and Holmes, 2002;Leyrer et al, 2013). Nonetheless, understanding what is influencing mortality rates during trans-Saharan flights, and during flights over geographic barriers more generally (e.g., Ward et al, 2018), is necessary to predict how changing conditions may impact the population dynamics of migratory species.…”
Section: Annual Cycle Eventmentioning
confidence: 99%
“…The extent to which an inhospitable area can act as a barrier can vary substantially and depends on several factors such as the migration strategy applied, environmental conditions and a bird's physiological condition (Bulte et al 2014, Gill et al 2014, Deppe et al 2015. Multiple studies conducted on songbirds and shorebirds showed that the success of crossing large inhospitable areas is closely tied to an individual's body condition and the occurrence of supporting winds during migration (Bulte et al 2014, Gill et al 2014, Duijns et al 2017, Ward et al 2018. Body condition also affects how birds navigate a barrier, for example through a higher propensity for crossing when having higher fuel loads and circumnavigating when the fuel loads are low (Schmaljohann and Naef-Daenzer 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The large‐scale nature of migration has made developing this understanding difficult, especially when determining the mortality rates associated with different migratory strategies (Shamoun‐Baranes et al ). However, with the advent of miniaturised tracking devices and advanced survival analyses, we are now better able to study these associations in situ (Sillett & Holmes ; Strandberg et al ; Klaassen et al ; Lok et al ; Rockwell et al ; Ward et al ; Senner et al ). Although most of these studies have found evidence consistent with long‐standing predictions that migration is the most hazardous part of the migratory annual cycle, examples of other portions of the annual cycle exhibiting higher mortality rates also exist (Leyrer et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have hypothesised that numerous factors could lead to elevated mortality rates during migration, including the use of unfamiliar habitats and stopover sites, the high energetic costs of migration and the occurrence of inclement weather conditions, such as strong head winds, sandstorms and extreme rainfall (Newton ). Among these, and especially for migrations crossing large inhospitable geographical features that lack emergency stopover sites – like deserts and oceans – the amount and predictability of wind assistance during migration are thought to affect the success of migratory flights the most (Erni et al ; Shamoun‐Baranes et al ; Aurbach et al ; Ward et al ).…”
Section: Introductionmentioning
confidence: 99%